2015
DOI: 10.1080/19336918.2015.1005465
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins in Cell Migration

Abstract: mitogen-activated protein kinase; HCC, hepatocellular carcinoma; cdc42, cell division control protein 42; EGF, epidermal growth factor; EGFR, epidermal growth factor receptor; Sprouty2, Sprouty homolog 2; ROCK, Rho-associated protein kinase; PI3K, phosphatidylinositol-4, 5-bisphosphate 3-kinase; ICAM-1, intercellular adhesion molecule 1; VCAM-1, vascular cell adhesion molecule 1; ERK, extracellular signal-regulated kinase; MAPK, mitogen-activated protein kinase; eNOS, endothelial nitric oxide synthase; HUVECs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 134 publications
(118 reference statements)
3
45
0
1
Order By: Relevance
“…Since we recently identified that FRCs exhibit a type of apical to basolateral polarity, in order to secrete matrix components unilaterally into conduit structures (43), this may explain the lack of front to back polarity which would be required for cell migration. Although CD9 is important in other cell types for migration (65), our data indicate that in FRCs, CD9 is involved in cellcell connections, thereby contributing to the formation and preservation of the FRC network.…”
Section: Discussionmentioning
confidence: 69%
“…Since we recently identified that FRCs exhibit a type of apical to basolateral polarity, in order to secrete matrix components unilaterally into conduit structures (43), this may explain the lack of front to back polarity which would be required for cell migration. Although CD9 is important in other cell types for migration (65), our data indicate that in FRCs, CD9 is involved in cellcell connections, thereby contributing to the formation and preservation of the FRC network.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have indicated that tetraspanins can regulate the function of proteins involved in all aspects of cell migration 11 . For example, tetraspanins can directly interact with integrins and modulate their downstream signalling in response to migratory signals 54, 55 .…”
Section: Discussionmentioning
confidence: 99%
“…2B). The ability of cells to migrate strongly depends on a dynamic actin assembly [9] and the protein superfamily of tetraspanins such as CD63 was shown to be involved in cell migration and adhesion [10]. Other dynamic entities which co-cluster in the membrane with CD63-YFP can also be studied with this new method.…”
Section: Resultsmentioning
confidence: 99%